MANAJEMEN PERENCANAAN TATA RUANG PERPUSTAKAAN SMP NEGERI 8 PONTIANAK - Ayu Lestari; Sisilya Saman Madeten (Universitas Tanjungpura, 2020)
AbstractThis research discusses about Disign Spatial Management library of Junior high School 8 Pontianak. The purpose of this research is to know how about spatial management and efforts are made to improve the spatial management at library of Junior high School 8 Pontianak. The method used is qualitative that is demonstrated to describe and analyse phenomena, events based on the data obtained. Data collection is done by observation, interviews and documentation. The results showed that spatial management library of SMP 8 Pontianak for now still needs to be considered in the arrangement of the room, the condition of the library is less effective because many books are still located on the floor due to lack of Cabinets or bookshelves to store the library material and also the library becomes a place of the appearance of art, sports and laboratory equipment. So, the library looks narrow and makes students feel uncomfortable during their visit. As for the efforts that can be done for spatial management library of Junior High School 8 Pontianak is by looking from Google or other schools that can be used as a reference to organize the room for better. Keywords: Libraries, Management, Spatial, School